2022
DOI: 10.1080/01652176.2022.2079756
|View full text |Cite
|
Sign up to set email alerts
|

Swine coronaviruses (SCoVs) and their emerging threats to swine population, inter-species transmission, exploring the susceptibility of pigs for SARS-CoV-2 and zoonotic concerns

Abstract: Swine coronaviruses (SCoVs) are one of the most devastating pathogens affecting the livelihoods of farmers and swine industry across the world. These include transmissible gastroenteritis virus (TGEV), porcine epidemic diarrhea virus (PEDV), porcine respiratory coronavirus (PRCV), porcine hemagglutinating encephalomyelitis virus (PHEV), swine acute diarrhea syndrome coronavirus (SADS-CoV), and porcine delta coronavirus (PDCoV). Coronaviruses infect a wide variety of animal species and humans because these are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 237 publications
0
24
0
Order By: Relevance
“…Coronaviruses (CoVs) are existed widely among mammals and birds ( Tang et al, 2021 ). As globally important pathogens, zoonotic CoVs have a higher risk for cross-species transmission to humans and animals ( Thakor et al, 2022 ). We found that PDCoV can infect swines of different ages, while piglets are more susceptible.…”
Section: Discussionmentioning
confidence: 99%
“…Coronaviruses (CoVs) are existed widely among mammals and birds ( Tang et al, 2021 ). As globally important pathogens, zoonotic CoVs have a higher risk for cross-species transmission to humans and animals ( Thakor et al, 2022 ). We found that PDCoV can infect swines of different ages, while piglets are more susceptible.…”
Section: Discussionmentioning
confidence: 99%
“…Coronaviruses (CoV) are the most widespread positive-sense and single-stranded RNA viruses that infect wild and domestic animals as well as humans. The scientific community’s increasing interest in these viruses is due to their relevant economic impact and potential interspecies transmission [ 4 , 5 ]. Coronaviruses generally have a strong propensity to recombine and mutate, often allowing them to cross and overcome the host species barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Four of them belong to the alphacoronavirus genus—transmissible gastroenteritis coronavirus (TEGV), porcine respiratory coronavirus (PRCV), porcine epidemic diarrhea virus (PEDV), swine acute diarrhea syndrome coronavirus (SADS-CoV) —one to the betacoronavirus genus—porcine hemagglutinating encephalomyelitis virus (PHEV)—and one from to the deltacoronavirus genus—PDCoV [ 6 ]. Three of these (PEDV, TGEV and PRCV) have been described in European pigs [ 5 ]. PEDV is an RI-emerged alphacoronavirus responsible for acute enteric syndrome leading to malabsorption due to the atrophy of intestinal villus, diarrhea and vomiting [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, four SeCoVs have been identified, namely transmissible gastroenteritis virus (TGEV), porcine epidemic diarrhea virus (PEDV), porcine deltacoronavirus (PDCoV), and severe acute diarrhea syndrome coronavirus (SADS-CoV). Besides PDCoV, all other SeCoVs are alphacoronaviruses [ 10 ].…”
Section: Introductionmentioning
confidence: 99%